The chain reaction of carbon emission trading policy in efficiency and rebound: evidence from spatial perspective in China - Huan Wang; Yangyang Shen; Ting Luo; Fang Wang; Yunqiang Liu (Humanities & Social Sciences Communications)
Abstract Evaluating and improving environmental policies are significantly impacted by the question of whether increased energy efficiency results in an energy rebound effect. Utilizing carbon emission trading policies (CETP) as a quasi-natural experiment, this study created a spatial difference-in-differences (SDID) model with an endogenous spatio-temporal weight matrix. The analysis applied Chinese provincial panel data from 2008 to 2018 to assess the direct and spatial spillover effects of CETP on total factor carbon emissions efficiency (TCEE). On this premise, it is further explored to see if CETP causes the energy rebound (ER) effect via TCEE. It revealed that CETP exhibited positive spatial spillover effects on TCEE. Specifically, CETP was observed to enhance TCEE in pilot areas through green innovation (GI) but impede TCEE in neighboring regions due to siphoning and pollution haven effects. Further research, however, revealed that the CETP increased the ER in the pilot areas by improving the TCEE, causing the policy to fall into the trap of ineffective emission reduction, but it had a warning effect on the nearby areas. This study is of great significance for improving the emission reduction policy system and promoting the “dual carbon” goals.